Resource Allocation of Distributed Heterogeneous Network Based on CoMP Transmission - Jia Yu; Ye Wang; Shaohua Wu; Qinyu Zhang (Dianxin kexue)
Improving utilization of radio resource is a promising solution to alleviate the contradiction between increasing wireless communications demands and limited radio resources of wireless transmission. Coordinated multipoint （CoMP）based heterogeneous network （HetNet）has huge application prospects to improve the spectrum efficiency and energy efficiency, and therefore, has attracted constant attentions from not only academia and industry. The radio resource allocation for CoMP based HetNet was investigated, and a distributed resource schedule algorithm by means of cross-entropy method was proposed. Extensive simulations are conducted to verify the effectiveness of the proposed algorithm in terms of throughput, energy efficiency and user fairness.